Comparative Transcriptome Analysis of Genes Involved in Sesquiterpene Alkaloid Biosynthesis in Trichoderma longibrachiatum MD33 and UN32 - Qian, Xu; Jin, Hui; Chen, Zhuojun; Dai, Qingqing; Sarsaiya, Surendra; Qin, Yitong; Jia, Qi; Jin, Leilei; Chen, Jishuang (Frontiers in Microbiology, 2021)
Trichoderma longibrachiatum MD33, a sesquiterpene alkaloid-producing endophyte isolated from Dendrobium nobile, shows potential medical and industrial applications. To understand the molecular mechanisms of sesquiterpene alkaloids production, a comparative transcriptome analysis was performed on strain MD33 and its positive mutant UN32, which was created using Ultraviolet (UV) mutagenesis and nitrogen ion (N+) implantation. The alkaloid production of UN32 was 2.62 times more than that of MD33. 1024 differentially expressed genes (DEGs), including 519 up-regulated and 505 down-regulated genes, were identified. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed 139 GO terms and 87 biosynthesis pathways. Dendrobine, arguably the main sesquiterpene alkaloid the strain MD33 produced, might start synthesis through the mevalonate (MVA) pathway. Several MVA pathway enzyme-coding genes (hydroxy-methylglutaryl-CoA synthase, mevalonate kinase, and farnesyl diphosphate synthase) were found to be differentially expressed, suggesting that physical mutagenesis can disrupt genome integrity and gene expression. Some backbone post-modification enzymes and transcript factors were either discovered, suggesting the sesquiterpene alkaloid metabolism in T. longibrachiatum is a complex genetic network. Our findings help to shed light on the underlying molecular regulatory mechanism of sesquiterpene alkaloids production in T. longibrachiatum.